Pengaruh Pengetahuan dan Persepsi Pelaku UMKM Tentang Akuntansi Terhadap Penggunaan Informasi Akuntansi di Kabupaten Pinrang - Hernianti, Harun; wahyuni, wahyuni (Universitas Muhammadiyah Gresik, 2023)
This study aims to find out how the influence of the knowledge and perceptions of micro, small and medium enterprises about accounting on the use of accounting information in Pinrang Regency. The research method used is the quantitative method with the analytical tool using multiple linear regression analysis with the help of the SPSS application. The number of samples in this study were 60 MSME actors in Pinrang Regency.The results of the study show that the knowledge possessed by MSME actors in Pinrang Regency has a partial and significant effect on the use of accounting information. Perceptions of MSME actors have a partial and significant influence on the use of accounting information. Knowledge and perceptions of MSME actors simultaneously or jointly have a significant effect on the use of accounting information. The contribution made by the variables of knowledge and perceptions of MSME actors on the use of accounting information is 60%. This means that the variable knowledge and perceptions of MSME actors contribute 60% to the use of accounting information.